Respirometry increases cortisol levels in rainbow trout Oncorhynchus mykiss: implications for measurements of metabolic rate. Issue 5 (27th March 2017) - Murray, L.; Rennie, M. D.; Svendsen, J. C.; Enders, E. C.
Abstract : This study aimed to assess the extent to which chasing, handling and confining Oncorhynchus mykiss to a small respirometer chamber during respirometric experiments is stressful and affects metabolic measurements. The study observed increased cortisol levels in animals tested using a chase protocol and subsequent intermittent‐flow respirometry, suggesting that this procedural treatment may stress animals.